Rastafari reasoning and the Rastawoman : gender constructions in the shaping of Rastafari livity - Christensen, Jeanne (Lanham, Maryland : Lexington Books, 2014)
"Rastafari Reasoning and the RastaWoman: Gender Constructions in the Shaping of Rastafari Livity examines the complex ways that gender and race intersected in the shaping of a liberation movement propelled by conscious contact with an African spiritual ethos as it had evolved in the Caribbean. Jeanne Christensen proposes that Rastafari represents the most recent reworking of this spiritual ethos, referred to as African religiosity. The book contributes a new perspective to the literature on Rastafari, and through a historical lens corrects the predominant static view of Rastafari women. In certain Rastafari manifestations, a growing livity developed by Rasta men eventually excluded women from an important ritual called "Reasoning"--A conscious search for existential and ontological truth through self-understanding arrived at in group deliberation. Restoring agency to the RastaWoman, Christensen argues that RastaWomen, intimately in touch with this spiritual ethos, challenged oppressive structures within the movement itself. They skirted official restrictions, speaking out in public and written forums whenever such avenues presented themselves, and searched for their own truth through conscious intentional self-examination characteristic of the Reasoning ritual. With its powerful, theoretically informed narrative, Rastafari Reasoning and the RastaWoman: Gender Constructions in the Shaping of Rastafari Livity will appeal to students and scholars interested in religious transformation, resistance movements, gender issues, critical race studies, and the history and culture of the English-speaking Caribbean."--
African religiosity -- The Afro-Creole village -- Emergence of Rastafari -- Reasoning and the Rastaman woman -- Taking root -- "From the cross to the throne" -- The arrival of Rastawoman.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Women in the Rastafari movement -- Caribbean Area; Rastafari movement -- Caribbean Area; Feminism -- Caribbean Area; Feminism -- Religious aspects -- Rastafarians; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Comparative Religion; Electronic books